Positive psychological states and stress responses in caregivers of adults receiving an allogeneic bone marrow transplant: A study protocol. (18th January 2021) - Tan, Kelly R.; Santacroce, Sheila J.; Wood, William A.; Mayer, Deborah K.; Santos, Hudson; Mucha, Peter J.; Schwartz, Todd A.; Fredrickson, Barbara L.
Abstract: Aims: This protocol directs a study that aims to: (a) describe the caregiver's experience over 8–12 weeks after an index adult patient's allogeneic bone marrow transplant (BMT) for advanced cancer using a case‐oriented approach and mixed methods, with qualitative methods in the foreground; and (b) e xplore networks of relationships among psycho‐neurological symptoms, positive psychological states and caregiver health. Design: Case‐oriented longitudinal design using multiple data types and analytic approaches. Methods: Data will be collected from 10–12 caregivers. The sample will be recruited from a large public hospital in the southeastern United States using maximum variation sampling (e.g., caregiver race/ethnicity, relationship to patient, age, education, and number of caregiving roles). Participants will be asked to complete weekly surveys, have their blood drawn bi‐weekly and participate in an interview each month during the study period ( 100 days). Aim 1 analysis will include directed content analysis and case‐oriented visual analysis. Aim 2 analysis will include symptom network estimation of psycho‐neurological symptoms, positive psychological states, and caregiver health. Institutional review board approval was obtained August 2018. Discussion: Results will provide an in‐depth description of caregivers' experiences in the 100 days after BMT. Findings will inform generation of hypotheses and identification of targets for interventions to improve caregiver's experiences after BMT. Impact: This in‐depth multi‐method longitudinal study to describe caregivers of adult patients receiving an allogeneic BMT is an essential step in understanding caregivers' complex responses to chronic stress and the role of positive psychological states. The results from this study will inform future research on chronic stress processes, intense caregiving, and intervention development. 摘要: 目的: 本方案为研究提供指导, 旨在: (a) 采用以病例为导向的方法和混合法, 描述护理人员在成年癌症晚期患者异基因骨髓移植 (BMT) 后8‐12周内的护理经验及定性方法; 以及 (b) 探索心理神经症状、积极心理状态和照料者健康之间的关系网络。 设计: 采用多种数据类型和分析方法的面向案例的纵向设计。 方法: 数据将由10‐12名护理人员提供。样本取自美国东南部的一家大型公立医院, 采用最大变异抽样 (例如, 护理人员的种族/民族、与患者的关系、年龄、教育程度和护理人员的数量) 方法。经要求, 参与者将应完成每周调查, 每两周抽一次血, 并应在研究期间 (约100天) 参加访谈, 频率控制在每月一次。目标1分析将包括定向内容分析和案例可视化分析。目标2分析将包括心理神经症状、积极心理状态以及护理人员健康症状网络评估。机构审查委员会于2018年8月获得批准。 讨论: 可通过研究结果对护理人员在骨髓移植后100天的经历进行深入描述。研究结果将有助于提出假设并确定干预目标, 以便改善护理人员在骨髓移植后的经历。 影响: 此项多方法纵向研究较为深入, 旨在对接受同种异体骨髓移植的成年患者护理人员进行描述, 是了解护理人员复杂慢性应激反应和积极心理状态作用的重要一步。本研究结果将有助于未来慢性应激过程、高强度护理和干预发展研究。